2019
DOI: 10.1093/ehjcr/ytz095
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular tachycardia in patients with type 1 myotonic dystrophy: a case series

Abstract: Background Type 1 myotonic dystrophy (DM1) is associated with a variety of cardiac conduction abnormalities and the frequent need for permanent pacing. However, the role of ventricular tachycardia (VT) and the implied risk of sudden cardiac death (SCD) is poorly understood. Case summary This study examined a 56-patient DM1 cohort of men and women, and identified five patients (two females and three males) with ventricular arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 12 publications
(13 reference statements)
0
17
0
Order By: Relevance
“…A total of six articles (four for CCAs, three for CRAs, and four for SCD) satisfied the criteria to be included in the metanalysis [12,13,18,23–25]. Out of 2047 DM1 patients reported (985 males, 1062 females), 430 men and 371 women presented a CCA (OR = 1.48; 95% CI = 1.23–1.77; Z test for overall effect = 4.24, p < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…A total of six articles (four for CCAs, three for CRAs, and four for SCD) satisfied the criteria to be included in the metanalysis [12,13,18,23–25]. Out of 2047 DM1 patients reported (985 males, 1062 females), 430 men and 371 women presented a CCA (OR = 1.48; 95% CI = 1.23–1.77; Z test for overall effect = 4.24, p < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…(Nikhanj, Yogasundaram, et al, 2020 ) Patients with DM1 were distinguishable given their high prevalence of conduction disease and incidence of arrhythmias, as shown in previous research. (Benhayon et al, 2015 ; Nikhanj, Miskew‐Nichols, Sivakumaran, et al, 2019 ; Nikhanj, Sivakumaran, Yogasundaram, et al, 2019 ) Given that QRS interval progression has been shown to correlate with reduced LV systolic function, 40 CRT remains an important therapy to restore ventricular synchrony in the setting of LBBB, which can be supported with beta‐blocker therapies in patients with ventricular tachyarrhythmias, as we have previously investigated in patients with DM1. (Nikhanj, Sivakumaran, Yogasundaram, et al, 2019 ) The severity and progression of conduction disease in patients with DM1 correlate with age and with the quantity CTG repeats, which supports the supplementation of demographics and genetic testing into the risk stratification of patients with DM1 in addition to baseline ECG analysis.…”
Section: Discussionmentioning
confidence: 98%
“…Importantly, VT is common in patients with DMD and DM1 including the risk of sudden cardiac death, which can be mitigated through the use of prophylactic device intervention as provided to our patients. (Nikhanj, Miskew‐Nichols, Sivakumaran, et al, 2019 ; Nikhanj, Sivakumaran, Yogasundaram, et al, 2019 ; Nikhanj, Yogasundaram, et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Her facial appearance and calvities were characteristic of myotonic dystrophy type 1, and circulatory events in the ICU were also keys for diagnosis. Some reports have suggested that fatal arrhythmias, such as ventricular tachycardia and Vf, and takotsubo syndrome are often clues for the diagnosis of myotonic dystrophy type 1 [ 4 6 ]. Since a genetic test is the only way to diagnose myotonic dystrophy type 1, we should not hesitate to perform genetic testing when we encounter a case that has difficulty recovering from respiratory failure.…”
Section: Discussionmentioning
confidence: 99%